The Hippodamian Plan: a Mesopotamian Origin? - Battini, Laura (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2018)
Classical historians and archaeologists maintain the idea that hippodamian plan is an invention of the Greek coast of Turkey. Called ‘hippodamian’ in honour of the Greek architect Hippodamos of Miletus who is considered the inventor of this plan, or ‘miletusian’ in honour of the city of Hippodamos, or more seldom ‘checkered’ in reason of the play board’s lines, this plan presents orthogonal streets intersected between them to form regular – square or rectangular – blocks of houses. This plan would be so seen as a pure result of the Greek rationality who appears in the will of organizing town space rationally.